The Effect Of Work Motivation And Work Discipline On Employee Performance At PT. Bank Rakyat Indonesia KC Soekarno – Hatta Airport - Yanuar, Rama; Santoso, Arief Budi (Pascasarjana STIE Miftahul Huda, 2025)
This study aims to determine and analyze the magnitude of the Influence of Work Motivation and Work Discipline on Employee Performance at PT Bank Rakyat Indonesia KC Soekarno-Hatta Airport partially and simultaneously. The research method used in this study is Quantitative research. The population used in this study were employees of PT Bank Rakyat Indonesia KC Soekarno-Hatta Airport. The sampling method used by the author in this study is the saturated sample method, where the sample is employees of PT Bank Rakyat Indonesia KC Soekarno-Hatta Airport totaling 65 employees. The data collection method used in this study is primary data. The primary data taken is data from the answers of respondents totaling 65 respondents. The results of this study indicate that Work Motivation has a partial effect on employee performance at PT Bank Rakyat Indonesia KC Soekarno-Hatta Airport which has been proven by the value of the results of t count> t table or (2.594> 1.998). Work discipline has a partial effect on employee performance at PT Bank Rakyat Indonesia KC Soekarno-Hatta Airport, the results of t count> t table or (2.594> 1.998) this is also reinforced by the results of the sig value <0.05 or (0.012 <0.05). Work motivation and work discipline have a simultaneous effect on employee performance at PT Bank Rakyat Indonesia KC Soekarno-Hatta Airport which has been proven by F count> F table or (139.625> 3.145) this is also reinforced by the sig value <0.05 or (0.000 <0.05).